2007
DOI: 10.1620/tjem.212.151
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal Exposure to 3,3',4,4',5-Pentachlorobiphenyl (PCB126) Promotes Anxiogenic Behavior in Rats

Abstract: and FUJIWARA, M. Prenatal Exposure to 3,3′,4,4′, Promotes Anxiogenic Behavior in Rats. Tohoku J. Exp. Med., 2007, 212 (2), [151][152][153][154][155][156][157] Polychlorinated biphenyls (PCBs) are environmental contaminants that have adverse effects on the endocrine and nervous systems. As they are still detected in breast milk and adipose tissue in humans, the accumulated PCBs may transfer from mothers to children and damage central nervous system. It is revealed from epidemiological studies that cognitive and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 35 publications
0
18
1
Order By: Relevance
“…Orito et al (2007) exposed female rat dams orally at GD15 to 30 μg/kg/day of PCB-126 in corn oil. At 4–5 weeks of age, they assessed male offspring by use of an open field test.…”
Section: Neurological Effectsmentioning
confidence: 99%
“…Orito et al (2007) exposed female rat dams orally at GD15 to 30 μg/kg/day of PCB-126 in corn oil. At 4–5 weeks of age, they assessed male offspring by use of an open field test.…”
Section: Neurological Effectsmentioning
confidence: 99%
“…In some cases the effects were still measurable in school-age children even though exposure levels declined substantially after weaning, suggesting that the neurotoxicity associated with prenatal exposure may have long-term implications. These findings are further supported in a number of mammalian studies demonstrating that developmental exposure to dioxins and dioxin-like PCBs resulted in impairment of advanced brain functions such as learning and memory, deficits in socioemotional behavior, and increased anxiety in response to mild stress, occurring at the juvenile and/or adult stages (Hany et al, 1999, Jolous-Jamshidi et al, 2010, Kakeyama et al, 2014, Kakeyama and Tohyama, 2003, Nguyen et al, 2013a, Orito et al, 2007, Piedrafita et al, 2008, Schantz and Widholm, 2001, Zimmer et al, 2009). However, the full potential for later-life neurobehavioral effects that result from early-life low level exposure to dioxin-like compounds is not well understood.…”
Section: Introductionmentioning
confidence: 53%
“…Wong et al (2010) tested this hypothesis on zebrafish intra-session (short-term) habituation to the novel tank assay using pentylenetetrazole (PTZ) and caffeine as known anxiogenic drugs, and found that habituation was strongly attenuated by acute exposure to either drug. Orito et al (2007) tested for effects of prenatal exposure to PCB126 on anxiogenic behavior in young (pre-puberty) rats using the open field and social interaction tests. The open field test, similar to the novel tank assay, is a stress-promoting situation with subjects tested individually, while the social interaction test examines interactive behavior of the tested subject with a novel partner as a measure for general anxiety level.…”
Section: Discussionmentioning
confidence: 99%
“…also found that genes related to cellular stress, cell cycle arrest, apoptosis, DNA repair, and oxidative stress were downregulated, such as mouse double minute 2 homolog and p53 following in vitro exposure of male samples to PCB 138 and PCB 180. Indeed, exposures to PCBs are associated to sex specific behaviors and cerebellar development, with greater effects in males (Boix et al, , 2011Nguon et al, 2005a,b;Orito et al, 2007;Roegge et al, 2000;Viberg et al, 2004).…”
Section: Discussionmentioning
confidence: 99%